Entre o engajamento e o desbunte: resistencia e deboche no Pasquim (1969-1979) - Natali Gisele de Oliveira (2007)
This text presents some considerations about the sense of weekly newspaper Pasquim in Brazil between 1969 and 1979. The Pasquim begins a contestation speech of the cultural, social and political Brazilian conditions. Emphasizing its important participation to understand the Brazilian culture at the 1970s, choose to simulate its style, language and some of the irreverent and mocking representations which were used like an alternative method of resistance to the traditional ways of political and social criticism establishing an especially harsh critique of the instituted customs, challenging the political impositions and, above all, evading daily authoritarianism. We appearing with the relying upon of the Pasquim trying make of a new politics concept ruled in the retaking subjective aspects to the political experience, in the value of the daily, the personal relationships and the behavior, the statement of the experiences peculiar of life, based in the criticism to the traditional concept of political representation (supporting or syndical) because it destroyer the particular ways of community or group and make a possibility of speak an own condition of life, with a political speech witch elaborated a private identity. Through dialogue as the countercultural idea, adapted at the Brazilian reality, notice in Pasquim its posture like an original suggestion to intervene by using new and different ways of critique and which granted us the opportunity to express the reality, without relying upon traditional and outdated models of politics.